Identification and evaluation laboratory hazards in Yazd University of Medical Sciences by standard checklists - GH Halvani; R Soltani; M Alimohammadi; Z Kiani (طب کار)
Abstract Background: The aim of this study is identification and evaluation of laboratories hazards in Yazd Medical Sciences University. Methods: This is a descriptive analytic study that was done to identify hazards of laboratories of Yazd Medical Science Universities in 2009.The instrument used for data collection was standardized checklists that before were used in 20 international organizations and 30 reliable laboratories in world, and their reliability and validity were confirmed. The kind of hazards were separated and systematized in these checklists and hardware, human, instruction, and environmental errors were separated from each other qualitative method was applied for evaluation. Results: According to results, main deficiencies were related to management failure and other defects in order of preference were lack of suitable ventilation, Lack of heating and cooling systems in the laboratory, Lack of safe work instructions and Lack of physical space. Conclusion: This study showed that the laboratories of universities have many defects and hazards, then adverse events and high probability of occurrence and certainly will be dire consequence, considering the high risk of events is necessary in the short term parallel administrative measures taken in this regard.